`y = (x^2 - 6)^3` Find the derivative of the function.

Textbook Question

Chapter 2, Review - Problem 54 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

hkj1385's profile pic

hkj1385 | (Level 1) Assistant Educator

Posted on

Note:- If y = x^n ; where n = constant ; then dy/dx = n*{x^(n-1)}

Now, 

`y = (x^2 - 6)^3`

`thus, dy/dx = y' = 3*{(x^2 - 6)^2}*(2x)`

`or, dy/dx = y' = 6x*(x^2 - 6)^2`

``

We’ve answered 318,949 questions. We can answer yours, too.

Ask a question